2001
DOI: 10.1103/physrevd.63.125008
|View full text |Cite
|
Sign up to set email alerts
|

Self-dual models and mass generation in planar field theory

Abstract: We analyse in three space-time dimensions, the connection between abelian self dual vector doublets and their counterparts containing both an explicit mass and a topological mass. Their correspondence is established in the lagrangian formalism using an operator approach as well as a path integral approach. A canonical hamiltonian analysis is presented, which also shows the equivalence with the lagrangian formalism. The implications of our results for bosonisation in three dimensions are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…This can be easily verified from the rule of degrees of freedom counting for the constrained systems. Another remarkable aspect is the symplectic structure (19). Though both x 1 and x 2 are real their Dirac bracket is complex.…”
Section: R Banerjee and P Mukherjeementioning
confidence: 99%
See 2 more Smart Citations
“…This can be easily verified from the rule of degrees of freedom counting for the constrained systems. Another remarkable aspect is the symplectic structure (19). Though both x 1 and x 2 are real their Dirac bracket is complex.…”
Section: R Banerjee and P Mukherjeementioning
confidence: 99%
“…From the symplectic structure (19) it is evident that −2iωx 2 is the conjugate momentum to x 1 . Now consider the canonical transformation to (x + , p + ), where…”
Section: R Banerjee and P Mukherjeementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in Refs. [43,44] it is shown that the MCS-Proca model describes a topological mass mix with two massive degrees of freedom, with masses √ b 2 + m 2 ± |b|. According to the GU method, we consider the constraint (4) as the first-class constraint (fcc) and the remaining constraint (3) as the corresponding canonical gauge condition.…”
Section: The Mcs-proca Modelmentioning
confidence: 99%
“…The generalized MCS-Podolsky model [38,41] is a such theory and was introduced in order to smooth ultraviolet singularities. Starting from the observation that the study of Einstein-Chern-Simons-Proca massive gravity (ECSPMG) (the Lagrangian of ECSPMG is the sum of the Einstein, (third derivative order) CS and Procalike mass terms) [42] is often accompanied [39,40,43] by the analysis of the MCS-Proca model (a non-higher derivative model) [37,38,[43][44][45], we consider a model described by Lagrangian action containing the Maxwell term, a higher derivative extension of the CS topological invariant [36], and a Proca mass term…”
Section: Introductionmentioning
confidence: 99%